The effect of the cannabinoid receptor agonist and antagonist on the light-induced changes in the suprachiasmatic nucleus of rats - Filipovská, Eva; Červená, Kateřina; Moravcová, Simona; Novotný, Jiří; Kyclerová, Hana; Spišská, Veronika; Pačesová, Dominika; Bendová, Zdeňka (Neuroscience letters, 2019)
The CB1 cannabinoid receptors have been found in the rodent suprachiasmatic nucleus, and their activation suppresses the light-induced phase shift in locomotor rhythmicity of mice and hamsters. Here, we show that the CB1 receptor agonist CP55940 significantly attenuates the light-induced phase delay in rats as well. Furthermore, it blocks the light induction of c-Fos and light-induced downregulation of pERK1/2 in the SCN, and the CB1 antagonist AM251 prevents the photic induction of pERK1/2 and reduces pGSK3β after photic stimulation. Our data suggest that the modulation of the cannabinoid receptor activity may affect the photic entrainment via the setting of the SCN sensitivity to light.
Keywords: potkani Wistar; agonisté kanabinoidních receptorů; antagonisté kanabinoidních receptorů; Cannabinoid Receptor Agonists; Rats, Wistar; zvířata; Animals; světlo; piperidiny; Male; Pyrazoles; mužské pohlaví; Cyclohexanols; Cannabinoid Receptor Antagonists; pohybová aktivita; Light; nucleus suprachiasmaticus; cyklohexanoly; Piperidines; Motor Activity; Suprachiasmatic Nucleus; pyrazoly